S100A4 expression in the enteric nerve system of young and aged rats - Fan Xiaoyi; Han Yiman; Xia Tianhao; Huang Kesheng; Xiang Zhenghua; Yuan Hongbin (Molecular Biology Reports, 2026)

Unraveling contrasting summer endogenous nutrient release regimes in Two Karst Plateau Lakes: Evidence from high-resolution measurements - Ye Zheng; Kun Wang; Jianyin Huang; Hongbin Yin; Chao Han (Water Research, 2026)

Macrophyte-to-algae transition: Suspended particulate matter mediates the bioavailability and retention of heavy metal(loid)s in the sediment - Wenxuan Han; Yiheng Du; Xue Sun; Zhaode Wang; Lei Zhang; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Journal of Environmental Chemical Engineering, 2026)

Engineering synergistic Brønsted–Lewis sites in MFI zeolite via atomic niobium dispersion for selective alkylation to durene - Jialun Shi; Yuncai Liu; Xin Pu; Xin Han; Lei Ye; Xinglong Qin; Hongbin Zhang; Jichang Liu (Chemical Engineering Journal, 2026)

ZNF200 and DDX17 regulatory loop promotes tumor growth and metastasis by activating RBPJ transcription in non-small cell lung cancer - Yanke Zhang; Hongbin Zhu; Xueqin Wang; Wei Dong; Maoyu Zhang; Xinyue Song; Danye Han; Qian Chai; Xueyi Feng; Xiaozheng Wei; Hongyu Chen; Yonghuai Li; et al. (Science China Life Sciences, 2026)

Research on the Highly Efficient and Low-Dose Improvement of Alcohol-Induced Liver Injury by High-Selenium-Content Modified Lycium barbarum Polysaccharides - Shuangzhe Mao; Xin Zhang; Lulu Wei; Han Zhang; Abo Li; Mengmeng Sun; Jiao Feng; Ting Ren; Yiting Huang; Xiaoying Liu; Zhifeng Zhang; Zhihui Zhao; et al. (Biological Trace Element Research, 2026)

Continuous plastic film mulching reduces global warming potential (GWP) in greenhouse soil biosolarization by regulating microbial carbon and nitrogen metabolism - Qianru Liu; Qiang Zuo; Yuteng Qi; Yufan Yang; Guochun Ding; Mao Li; Guicheng Han; Yinzhi Chu; Bingxue Wang; Yuhao Sun; Xiao Zhao; Lianfeng Du; et al. (Journal of Cleaner Production, 2026)

Modulating the strength-bulk balance in bamboo chemical thermomechanical pulp via lignin-carbohydrate interactions: Constructing carbon‑carbon and hydrogen bonds - Jian Jiao; Xiu Wang; Ting Jiao; Shanming Han; Hongbin Li; Yongjun Deng; Guigan Fang; Chen Su (Chemical Engineering Journal, 2026)

Delocalized-electron engineered 2D mesoporous COFs boosting interfacial desolvation toward low-temperature zinc metal batteries - Yidan Duan; Yongzheng Zhang; Zhiyan Wang; Yue Liu; Rui Han; Cheng Ma; Duan Bin; Hongbin Lu; Wenming Qiao; Jitong Wang; Licheng Ling (Chemical Engineering Journal, 2026)

Multicompartment decoupling imaging (MDI): a technical breakthrough enabling quantitative mapping of the cellular, vascular, and extracellular space diffusion in the human brain - Hongbin Han (Science China Life Sciences, 2026)

Global-to-regional variations in the effects of grassland management on soil carbon - Xi Lin; Shengwei Zhang; Alfredo Huete; Han Y.H. Chen; Hongbin Zhao; Qinsi He; Shengwei Lv; Qian Zhang; Xiaoduo Zhang; Xiaofeng Zhang (Agriculture, Ecosystems & Environment, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Organic matter cycling reveals escalating algal blooms and accelerated mineralization in a macrophyte-dominated cold-arid eutrophic lake - Fengrui Zhang; Wenxuan Han; Xue Sun; Zhaode Wang; Lei Zhang; Qiushi Shen; Haijin Lan; Bingfa Chen; Hongbin Yin; Cheng Liu (Water Research, 2026)

Mechanistic insights and application of SS/MS/C/CaO₂ composite for the simultaneous removal of ammonia nitrogen and multiple antibiotics - Jie Zhao; Chang Lu; Junzhao Liu; Yuze Han; Xiuwen Li; Jun Li; Wentao Li; Hongbin Xu; Jingqing Gao; Aimin Li; Shuqing An (Water Research, 2026)

Fine-scale evaluation on phosphorus dynamics in sediments of Hongjian Nur, the largest desert lake in China - Xinyue Guo; Wenquan Liu; Chao Han; Odsuren Batdelger; Narangerel Serdyanjiv; Hongbin Yin (Water Research, 2026)

Simultaneous Removal of Nitrate and Typical Antibiotics Using Fe/MS/C Composite: Performance, Mechanism, Ecological Impact, and Practical Application - Jie Zhao; Junzhao Liu; Yuze Han; Chang Lu; Jun Li; Wentao Li; Hongbin Xu; Jingqing Gao; Aimin Li (Water Research, 2026)

Radical-Net: A chemistry-enhanced transformer for elementary radical reactions in pollutant chemistry - Zhi Huang; Jiang Yu; Wei He; Pengxinyue Huang; Siwei Deng; Hongbin Jiang; Jie Yu; Chun Yang; Cheng Han; Yinying Jiang; Weiwei Zhu; Yucheng Liu (Journal of Hazardous Materials, 2026)

Spatial prediction and dynamic change of soil organic carbon using remote sensing variables as auxiliary information in wavy plain, Northeast China - Tianyi Shao; Fengkui Qian; Shuai Wang; Zhuodong Jiang; Hongbin Liu; Rattan Lal; Wei Han (Soil and Tillage Research, 2025)

Effects of organic fertilizer substitution for chemical fertilizer on tea yield and quality: A meta-analysis focusing on alkali-hydrolyzable nitrogen dynamics - Shaobo Zhang; Hongbin Zhang; Lan Zhang; Zhengzhen Li; Yihu Mao; Liping Zhang; Shibei Ge; Qiang Hu; Chao Chen; Wenyan Han; Peng Yan; Xin Li (Soil and Tillage Research, 2025)

Synergy of algal particle deposition and bioturbation amplifies the internal phosphorus loading - Fengrui Zhang; Lixian Tan; Wenxuan Han; Lei Zhang; Qiushi Shen; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Water Research, 2025)

Investigation of the interfacial binding capacity and mechanism between char layer and pyrolytic/virgin layer of silicone rubber-based composites after ablation - Hongbin Tian; Zhao Lu; Zhaohui Lu; Xinyang Luo; Hang Ye; Shitian Han; Changbin Pan; Liwei Yan; Huawei Zou; Shengtai Zhou (Chemical Engineering Journal, 2025)

Precise Magnetic Stimulation of the Paraventricular Nucleus Improves Sociability in a Mouse Model of ASD - Sha Liu; Quyang Yang; Pengfei Zhu; Xuan Liu; Qingbo Lu; Jie Yang; Jingyao Gao; Hongbin Han; Zhijun Zhang; Ning Gu; Tao Tan; Jianfei Sun (Neuroscience Bulletin, 2025)
Magnetic stimulation has made significant strides in the treatment of psychiatric disorders. Nonetheless, current magnetic stimulation techniques lack the precision to accurately modulate specific nuclei and cannot realize deep brain magnetic stimulation. To address this, we utilized superparamagnetic iron oxide nanoparticles as mediators to achieve precise targeting and penetration. We investigated the effects of magnetic fields with varying frequencies on neuronal activity and compared the activation effects on neurons using a 10-Hz precise magneto-stimulation system (pMSS) with repetitive transcranial magnetic stimulation in mice. Oxytocin levels, dendritic morphology and density, and mouse behavior were measured before and after pMSS intervention. Our findings suggest that pMSS can activate oxytocinergic neurons, leading to upregulation of oxytocin secretion and neurite outgrowth. As a result, sociability was rapidly improved after a one-week pMSS treatment regimen. These results demonstrate a promising magneto-stimulation method for regulating neuronal activity in deep brain nuclei and provide a promising therapeutic approach for autism spectrum disorder.

Enhanced effects of LMA combined with Vallisneria spiralis in controlling sediment organic phosphorus: The pivotal role of submerged macrophytes roots - Tianlun Han; Yan Wang; Meijun Bao; Wanzhong Wang; Hongbin Yin; Jian Li; Yi Zhang; Ming Kong (Journal of Environmental Chemical Engineering, 2025)

Community stability of free-living and particle-attached prokaryotes in coastal waters across four seasons: insights from 9.5 years of weekly sampling - Sangwook Scott Lee; Han Seul Lee; Zhimeng Xu; Masayuki Ushio; Xiaodong Zhang; Hongbin Liu (Marine Pollution Bulletin, 2025)

Revealing the effects and mechanisms of lake autochthonous dissolved organic matter on phosphorus sequestration by lanthanum-modified clay at the molecular level - Tianlun Han; Yan Wang; Minhui Cai; Hongbin Yin; Huacheng Xu; Ming Kong (Journal of Environmental Management, 2025)

Multi-factor interaction perspective: machine learning-based analysis of Ni2⁺ adsorption onto soil - Yingdong Wu; Jiang Yu; Zixin Zeng; Zhi Huang; HongBin Jiang; Pu Wang; Siwei Deng; Lei Han; Xinyue Huangpeng; Yinying Jiang; Weiwei Zhu (Environmental Geochemistry and Health, 2025)

Adaptive fuzzy optimal attitude control for AUVs with input nonlinearity - Yuliang Wang; Yiping Li; Xinhui Zheng; Han Bao; Chunlei Guo; Hongbin Zhang (Ocean Engineering, 2025)

The strategy of crushing and re-granulation promoted anammox granular sludge (AnGS) formation and performance improvement - Hongbin Zhu; Ji Zhao; Jiaxiang Nie; Zhipeng You; Han Xiang; Yanling Qiu; Juan Feng; Xiaoxia Wang (Chemical Engineering Journal, 2025)

Mechanism Analysis of Selenium-Containing Compounds in Alleviating Spinal Cord Injury Based on Network Pharmacology and Molecular Docking Technology - Wen Han; Ling Xie; Chaochao Ding; Dandan Dai; Nan Wang; Jianmin Ren; Hailin Chen; Suyan Zhu; Jian Xiao; Hongbin Xu (Molecular Neurobiology, 2025)

Study on cooling efficiency and mechanism of lithium-ion battery thermal runaway inhibition by additives enhanced water mist based on boiling heat transfer theory - Xiangming Hu; Zhiyuan Yang; Yurui Deng; Ming Li; Qingsong Wang; Hongbin Wei; Xiaoxuan Wei; Guoyu Han (Process Safety and Environmental Protection, 2024)

Attitude Practical Stabilization of Underactuated Autonomous Underwater Vehicles in Vertical Plane - Yuliang Wang; Han Bao; Yiping Li; Hongbin Zhang (Journal of Marine Science and Engineering, 2024)
Due to the singularity of Euler angles and the ambiguity of quaternions, to further expand the attitude reachable range of underactuated AUVs in the vertical plane, SO(3) is used to represent the attitude change of underactuated AUVs. The transverse function of the attitude on SO(3) is designed, and the exponential mapping method is used to construct the attitude kinematic controller of underactuated AUVs. Considering the changes in the model and ocean current during motion, interval type II fuzzy systems (IT2-FLSs) are used to estimate these changes. The backstepping method and the small gain theorem are adopted to design dynamic controllers to ensure the stability and robustness of the system. A novel saturation auxiliary system is designed to compensate for the influence of actuator saturation characteristics. Finally, the simulation results verify the effectiveness of the proposed controller and ensure the practical stabilization of the underactuated AUV attitude.

A novel neuroprotective method against ischemic stroke by accelerating the drainage of brain interstitial fluid - Jingge Lian; Liu Yang; Hanbo Tan; Shaoyi Su; Leonor Serrano Lopes; Fangxiao Cheng; Junhao Yan; Yu Fu; Wanyi Fu; Zhaoheng Xie; Jianfei Sun; Jicong Zhang; et al. (Science China Life Sciences, 2024)

Combination of lanthanum-modified attapulgite and Vallisneria natans for immobilization of phosphorus in various types of sediments - Ming Kong; Xinya Ouyang; Tianlun Han; Wanzhong Wang; Hongbin Yin; Yan Wang (Chemical Engineering Journal, 2024)

Three-dimensional analysis and drivers of relationships among multiple ecosystem services: A case study in the Nansi Lake Basin, China - Hongbin Sang; Yang Liu; Zhixian Sun; Wenying Han (Environmental Impact Assessment Review, 2024)

Reduced moisture caused by short-term grazing prohibition results in a significant decrease of fungi abundance - Hongbin Zhao; Xiaofu Zhang; Huiyan Liu; Xue Bai; Jiaming Nie; Guodong Han; Bing Han (Journal of Arid Environments, 2024)

Deep integration of pyrolysis kinetics and pyrolysis mechanism of polyimide aerogels - Xiangming Hu; Hongbin Wei; Yurui Deng; Zhiyuan Yang; Xiaoxuan Wei; Guoyu Han (Fuel, 2024)

Assessment of Hydrodynamic Performance and Motion Suppression of Tension Leg Floating Platform Based on Tuned Liquid Multi-Column Damper - Fuyin Cui; Shuling Chen; Hongbin Hao; Changzhi Han; Ruidong Ni; Yueyue Zhuo (Journal of Marine Science and Engineering, 2024)
To address the unstable motion of a tension leg platform (TLP) for floating wind turbines in various sea conditions, an improved method of incorporating a tuned liquid multi-column damper (TLMCD) into the TLP foundation is proposed. In order to evaluate the control effect of TLMCD on the motion response of the floating foundation, a multiphase flow solver based on a viscous flow CFD method and overlapping grid technique is applied to model the coupled multi-body dynamics interaction problem involving liquid tanks, waves, and a spring mooring system. This method has been proven to accurately capture the high-frequency motions of the structure and account for complex viscous interferences affecting the geometric motions. Additionally, the volume of fluid (VOF) method and the first-order linear superposition method are used to model the focused wave, enabling a simulation of the effects of transient wave loads on the floating foundation. The results show that the tuned damping effect of TLMCD on the TLP is mainly in the pitch motion, with the maximum pitch amplitude control volume ratio of TLMCD reaching up to 86% and the maximum surge amplitude control volume ratio of TLMCD reaching up to 25.2% under the operating conditions. These findings highlight the potential for additional research on and implementation of TLMCD technology.

Molecular identification and nutritional analysis of green tide algae in the coastal waters of Qinhuangdao, China - Yan Li; Xiaojun Ma; Meijie Jiang; Wei Song; Gang Wang; Hongbin Han (Frontiers in Marine Science, 2023)
Since 2015, the coastal waters of Qinhuangdao in Hebei province, China have experienced green tide disasters for consecutive years. Resource utilization is an important measure for preventing and controlling green tides. To comprehensively utilize green tide algae, this study first identified theses green tide algae and then assessed their nutritional value. Based on analysis of the internal transcribed spacer (ITS), 5S spacer regions (5S) and the mitochondrial cytochrome C oxidase I (COI), the dominant species were Ulva prolifera , Bryopsis plumose , Ulva australis , and Gracilariopsis lemaneiformis . The basic nutritional components, i.e., chlorophyll, amino acids, mineral elements, and heavy metal contents, of these four algae were measured and analyzed, and the four dominant species were shown to be high-nutrient-value marine foods with complete and reasonable protein, amino acid, and mineral compositions. This indicates that there is value in further research and development towards their utilization as nutrient sources. This study provides a basis for the comprehensive development and utilization of green tide algae resources in the coastal waters of Qinhuangdao.

Erratum to: Comparison of growth and nutrient uptake capacities of three domsinant species of Qinhuangdao green tides - Hongbin Han; Ruobing Wen; Hui Wang; Sheng Zhao (Acta Oceanologica Sinica, 2023)

NTPSS-vPower: A model for system simulation of a nuclear thermal propulsion system - Zhichao Qi; Wenbin Han; Minyun Liu; Chengzhi Ji; Hongbin Wei; Shanfang Huang (Annals of Nuclear Energy, 2023)

Tannic acid exerts antifungal activity in vitro and in vivo against Alternaria alternata causing postharvest rot on apple fruit - Haixia Wang; Lin Fu; Chunli Li; Xinlu Zhang; Kpadonou Essedolo Narcisse; Haishi Qi; Chuanyu Han; Xiangyu Wang; Hongbin Ma; Chunyu Zhu; Fangliang Zheng (Physiological and Molecular Plant Pathology, 2023)

Comparative review on microbial electrochemical technologies for resource recovery from wastewater towards circular economy and carbon neutrality - Shihai Deng; Chaoqi Wang; Huu Hao Ngo; Wenshan Guo; Na You; Hao Tang; Hongbin Yu; Long Tang; Jie Han (Bioresource Technology, 2023)

The Overwintering Capability of Ulva prolifera Spores and Gametes in the Yellow Sea, China - Hongbin Han; Sheng Zhao; Xiaoli Song; Hui Wang (Journal of Ocean University of China, 2023)

Comparison of growth and nutrient uptake capacities of three dominant species of Qinhuangdao green tides - Hongbin Han; Ruobing Wen; Hui Wang; Sheng Zhao (Acta Oceanologica Sinica, 2023)

Water hazard detection: A 20-year review - Xiaodong Guo; Jizhou Han; Jingyu Li; Zhoubo Wang; Zhenhai Zhang; Xiao Kang; Wei Zhu; Hongbin Deng (Journal of Terramechanics, 2023)

DLGAP1-AS2 promotes human colorectal cancer progression through trans-activation of Myc - Chunfeng Ren; Hongbin Han; Jingjing Pan; Qian Chang; Wanhai Wang; Xiaobing Guo; Jing Bian (Mammalian Genome, 2022)

Variations in nano- and pico-eukaryotic phytoplankton assemblages in the Qinhuangdao green-tide area - Weiqian Zhang; Hongbin Han; Limei Qiu; Chao Liu; Qingchun Zhang; Guizhong Zhou (Journal of Oceanology and Limnology, 2022)

Population differentiation in the dominant species (Ulva prolifera) of green tide in coastal waters of China - Hongbin Han; Yan Li; Xiaojun Ma; Wei Song; Zongling Wang; Mingzhu Fu; Xuelei Zhang (Acta Oceanologica Sinica, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Retraction Note: Mountainous atmospheric environment and characteristic products packaging design based on the enhanced technology of Internet of Things - Hongbin Han; Jingjing Zhao (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE: Mountainous atmospheric environment and characteristic products packaging design based on the enhanced technology of Internet of Things - Hongbin Han; Jingjing Zhao (Arabian Journal of Geosciences, 2021)

Safety evaluation and failure behavior of degraded tunnel structure with compound diseases of voids and lining defects - Wei Han; Yujing Jiang; Ningbo Li; Dairiku Koga; Osamu Sakaguchi; Hongbin Chen (Arabian Journal of Geosciences, 2021)

Comprehensive Marine Observing Experiment Based on High-Altitude Large Unmanned Aerial Vehicle (South China Sea Experiment 2020 of the “Petrel Project”) - Xuefen Zhang; Liangxu Li; Rongkang Yang; Ran Guo; Xia Sun; Jianping Luo; Hongbin Chen; Daxin Liu; Kebing Tang; Wenwu Peng; Xiaodong Han; Qiyun Guo; et al. (Advances in Atmospheric Sciences, 2021)

Brain interstitial fluid drainage and extracellular space affected by inhalational isoflurane: in comparison with intravenous sedative dexmedetomidine and pentobarbital sodium - Guomei Zhao; Hongbin Han; Jun Yang; Min Sun; Dehua Cui; Yuanyuan Li; Yajuan Gao; Jing Zou (Science China Life Sciences, 2020)

Roles of insulin-like growth factor II in regulating female reproductive physiology - Tahir Muhammad; Mengjing Li; Jianfeng Wang; Tao Huang; Shigang Zhao; Han Zhao; Hongbin Liu; Zi-Jiang Chen (Science China Life Sciences, 2020)

The contribution of attached Ulva prolifera on Pyropia aquaculture rafts to green tides in the Yellow Sea - Hongbin Han; Shiliang Fan; Wei Song; Yan Li; Jie Xiao; Zongling Wang; Xuelei Zhang; Dewen Ding (Acta Oceanologica Sinica, 2020)

Toll-Like Receptor 4 Promotes Th17 Lymphocyte Infiltration Via CCL25/CCR9 in Pathogenesis of Experimental Autoimmune Encephalomyelitis - Ying Zhang; Jingjing Han; Meili Wu; Lu Xu; Yu Wang; Wen Yuan; Fang Hua; Hongbin Fan; Fuxing Dong; Xuebin Qu; Ruiqin Yao (Journal of Neuroimmune Pharmacology, 2019)

Distribution of green algae micro-propagules and their function in the formation of the green tides in the coast of Qinhuangdao, the Bohai Sea, China - Hongbin Han; Wei Song; Zongling Wang; Dewen Ding; Chao Yuan; Xuelei Zhang; Yan Li (Acta Oceanologica Sinica, 2019)

Reassessment of an Arabidopsis cell wall invertase inhibitor AtCIF1 reveals its role in seed germination and early seedling growth - Tao Su; Sebastian Wolf; Mei Han; Hongbo Zhao; Hongbin Wei; Steffen Greiner; Thomas Rausch (Plant Molecular Biology, 2016)

Validation of the modified Becker’s split-window approach for retrieving land surface temperature from AVHRR - Weijun Quan; Hongbin Chen; Xiuzhen Han; Zhiqiang Ma (Journal of Meteorological Research, 2015)

An in vivo study with an MRI tracer method reveals the biophysical properties of interstitial fluid in the rat brain - HongBin Han; Kai Li; JunHao Yan; Kai Zhu; Yu Fu (Science China Life Sciences, 2012)

Simple diffusion delivery via brain interstitial route for the treatment of cerebral ischemia - HongBin Han; ZuoLi Xia; He Chen; Chao Hou; WeiBo Li (Science China Life Sciences, 2011)

Retrieval of aerosol optical properties over the Beijing area using POLDER/PARASOL satellite polarization measurements - Xuehua Fan; Hongbin Chen; Longfu Lin; Zhigang Han; Philippe Goloub (Advances in Atmospheric Sciences, 2009)